Chelidonium majus crude extract induces activation of peripheral blood mononuclear cells and enhances their cytotoxic effect toward HeLa cells. Issue 7 (3rd July 2022) - Popovic, Ana; Deljanin, Milena; Popovic, Suzana; Todorovic, Danijela; Djurdjevic, Predrag; Matic, Sanja; Stankovic, Milan; Avramovic, Dusko; Baskic, Dejan
ABSTRACT: The aim of the study was to examine the immunomodulatory effect of crude Chelidonium majus L ethanolic extract on ex vivo harvested peripheral blood mononuclear cells (PBMNCs). PBMNCs were isolated by density gradient centrifugation. The PBMNC cytotoxicity assay was performed with HeLa tumor cells as target cells. MTT assay was used to estimate the proliferation effect of extract and cytotoxic efficiency of treated PBMNCs. Flow cytometric analysis was used for immunophenotyping. Treatment induced moderate proliferative response, perturbation in PBMNC ratios, and the emergence of some unconventional subpopulations. The percentage ratio of double positive CD4+ and CD8+ T lymphocytes and monocytes, ratio of T and B lymphocytes expressing CD14, and percentage of NK cells expressing CD57 increased after treatment, indicating activation of PBMNC subpopulations. Cytotoxic activity against HeLa cells was enhanced. Activation of PBMNCs and enhancement of their cytotoxic effect toward HeLa cells indicate the immunostimulatory effect of Ch. majus ethanolic extract.